The Implementation and Evaluation of a Stock Epinephrine for Schools Program in Maricopa County, Arizona. - Broas, Erin; Lowe, Ashley A.; Ivich, Kimberly; Garcia, Melissa; Ward, Jackie; Hollister, James; Gerald, Lynn B. (Journal of School Nursing, 2024)
The increasing rate of food allergies in children, combined with the role of food as an integral part of the school day has led to the emergence of anaphylaxis as a daily threat to students, regardless of prior allergy diagnosis. Stock epinephrine—non-patient specific epinephrine auto-injectors that may be used during emergencies—is a means for schools to prepare for anaphylactic events and protect children with allergies. The Maricopa County Department of Public Health initiated the School Surveillance and Medication Program (SSMP), a data capture program, to facilitate the process of stocking epinephrine in schools. Spearheaded by the implementation efforts of the Kyah Rayne Foundation, program enrollment increased 146% between the 2020–2021 and 2021–2022 school years. The increased proportion of schools enrolled in the SSMP and the number of school personnel trained to administer epinephrine demonstrates the feasibility of school-centered stock epinephrine programs and validates strategies for increasing program uptake.